(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Nowadays, power control management plays a vital role in reducing consumption and increase the efficiency of resource utilization. In the traditional system, the manual operation of electrical devices in colleges gets unnoticed, which leads to high electricity consumption. To solve this problem, the proponents designed a scheduling power control system in two classrooms that will be equipped with a Radio Frequency Identification Device (RFID) that will cater to the occupants. These devices can switch on/off automatically. The RFID-based Power Control with Scheduling System is a centralized system that can be monitored and controlled by the administration and by the college department to find out the whereabouts in their system. The faculty staff/member can use the device by tapping their RFID/ID by turning on/off the power control device in the classroom. Teachers can use the classroom up to their last period and the system will automatically turn off the controller of the classroom. The researchers gathered information by using the engineering method to determine the analytical and logical approach to problem-solving that uses science, mathematics, and physics to define, analyze, and solve issues for the improvement of the existence of life on Earth. The researchers obtained the frequency and percentage of the gathered data to conclude the problem on where the researchers are focused and to know what is behind the problem of the College on their electric consumption. The significant increase in the electric bills is one of the major concerns of schools. The school management wants to know how can they save on electricity when classrooms require ventilation, light, and other electrical devices. Students occasionally forget to turn off the light or electric fan upon leaving the classroom, which may lead to even higher electricity consumption. This phenomenon results in inconsiderable energy misuse and overspending of resources. This situation calls for an automatic power control system to utilize electrical consumption.